An Updated Review on Phytochemical Properties of “Golden Dewdrop” Duranta erecta - Subsongsang, Rattawat; Jiraungkoorskul, Wannee (Pharmacognosy Reviews)
Duranta erecta (family: Verbenaceae) commonly referred to golden dewdrop, pigeon berry, angel whisper, or skyflower is one of the traditional medicinal plants. It has been shown to possess antimicrobial, antioxidant, and insecticide properties. Its phytoconstituents such as alkaloids, flavonoids, glycosides, phenolics, saponins, steroids, tannins, and terpenoids are reported as the basis of its efficacious therapeutic properties. The other important constituents which contribute to the remedial properties are durantol, pectolinaringenin, repennoside, repenins, and scutellarein. Published information on the phytochemical property of D. erecta was gathered by the use of different database platforms, including Google Scholar, ScienceDirect, PubMed, SciFinder, and Scopus, that provided an up‑to‑date review on its importance.
Keywords: Duranta erecta; golden dewdrop; phytochemical substance; plant; traditional medicine